2009
DOI: 10.1158/1078-0432.ccr-09-1354
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Biomarker Trial of Anastrozole or Low-Dose Tamoxifen or Their Combination in Subjects with Breast Intraepithelial Neoplasia

Abstract: Purpose: In the Anastrozole, Tamoxifen Alone or in Combination trial, the combination arm was inferior to anastrozole alone in terms of disease-free survival possibly due to an adverse pharmacokinetic interaction or a predominant estrogenic effect of tamoxifen under estrogen deprivation. We assessed whether the addition of a lower dose of tamoxifen influenced anastrozole bioavailability and favorably modulated biomarkers of bone fracture, breast cancer, cardiovascular disease, and endometrial cancer risk. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 51 publications
2
26
1
Order By: Relevance
“…In contrast, another small study of 32 patients with letrozole did show a reduction in estradiol levels (14). Similarly, Bonnani and colleagues showed a reduction in estradiol levels with anastrozole when combined with tamoxifen (17). Finally, a study by Prowell and colleagues that had a very similar cohort and design to our study, showed a reduction in estradiol levels after 6 months of anastrozole therapy (19).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, another small study of 32 patients with letrozole did show a reduction in estradiol levels (14). Similarly, Bonnani and colleagues showed a reduction in estradiol levels with anastrozole when combined with tamoxifen (17). Finally, a study by Prowell and colleagues that had a very similar cohort and design to our study, showed a reduction in estradiol levels after 6 months of anastrozole therapy (19).…”
Section: Discussionsupporting
confidence: 80%
“…However, Bonanni and colleagues evaluated the effect of 2 months of tamoxifen in different doses versus placebo in 110 healthy women and showed a reduction in IGF-1/IGFBP-3 (16). In another study of 75 postmenopausal patients that were randomized to tamoxifen 10 mg/week, anastrozole at 1 mg/d or the combination for 12 months showed also a reduction in IGF-1/IGFBP-3 levels in the combination arm compared with the anastrozole arm (17). Similar to these results, our study also showed a significant modulation in the IGF pathway, specifically, a significant increase in IGFBP-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (n = 12) of cohorts 41,73,83,87,93,96,97,[99][100][101]113,114 presented the rationale for the alleles tested for, with all but two 49,112 providing rationale for CYP2D6 per se. All described the test used for genotyping and/or the specific procedure, with TaqMan or AmpliChip being the most commonly used in 12 83 reported quality control methods and seven cohorts 87,91,96,97,104,114 reported on the Hardy-Weinberg equilibrium (two of these cohorts were reported in the same paper 114 ).…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…In around half (n = 12) of the cohorts it was clear there were missing genotype data, 41,82,83,87,[96][97][98][99][100][101]108,112 reasons being provided in seven of these. 82,83,87,97,99,108,112 Only three of the cohorts, all abstracts, 86,90,113 failed to present the number of patients contributing to each analysis.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…41 A multicentric clinical study aimed at validating this approach is ongoing in Italy. Our study has some limitations.…”
Section: Serrano Et Almentioning
confidence: 99%